Clase de diferenciación en latín. Significado posicional del adjetivo en el sintagma nominal (Argos, 2025)
The present paper shows a methodology of discourse analysis in classical languages from the perspective of a new linguistic current named "ethnopragmatics", which offers a boarding syntactic phenomena both qualitative and quantitative, so that it means a device descriptively surmounting former boardings. From this point of view, the positional variation of adjective in Latin noun phrase is interpreted as a communicative strategy moved by the action of context parameters.
Keywords: ethnopragmatics; linguistic variation; statistics; microsyntax; discourse analysis